A rapid genome-wide response to Drosophila melanogaster social interactions. - Carney, G.E. (BMC Genomics, 2007)
The actions and reactions integral to mate recognition and reproduction are examples of multifaceted behaviors for which we are only beginning to comprehend the underlying genetic and molecular complexity. I hypothesized that social interactions, such as those involved in reproductive behaviors, would lead to immediate and assayable changes in gene expression. Such changes may have important effects on individual reproductive success and fitness through alterations in physiology or via short-term or long-term changes in nervous system function.I used Affymetrix Drosophila Genome arrays to identify genes whose expression profiles would change rapidly due to the social interactions occurring during Drosophila melanogaster courtship. I identified 43 loci with significant expression profile changes during a 5-min exposure period. These results indicate that social interactions can lead to extremely rapid changes in mRNA abundance.The known functions of the up-regulated genes identified in this study include nervous system signaling and spermatogenesis, while the majority of down-regulated loci are implicated in immune signaling. Expression of two of the up-regulated genes, Odorant-binding protein 99b (Obp99b) and female-specific independent of transformer (fit), is controlled by the Drosophila sex-determination gene hierarchy, which regulates male and female mating behaviors and somatic differentiation. Therefore, additional identified loci may represent other long-elusive targets of Drosophila sex-determination genes.